(untitled) (Journal of science and technology exploration, 2026)
With the deep integration of technologies such as generative artificial intelligence, compliance governance in the banking sector is facing fundamental challenges arising from "algorithmic black boxes," model hallucinations, and data ethics. Based on representative practices in the global banking industry from 2024 to 2025, this study systematically analyzes the paradigm shift in AI-driven compliance governance—from "passive response" to "active embedding," and from "tool application" to "operating system-level capabilities." The analysis indicates that leading institutions are transforming compliance into a core competitive advantage by constructing automated governance frameworks covering the entire lifecycle, advocating for the ethical principle of "building trust through design," and promoting collaborative innovation within "regulatory sandboxes." The research suggests that the future competitiveness of the banking industry will depend not only on the diversity of technological applications but also on whether governance systems can internalize ethical constraints as technical foundations, thereby establishing a dynamic balance between innovation and stability.